The confused taxonomy of Pseudolaelia irwiniana (Orchidaceae) with two new synonyms - van Den Berg, Cassio; Menini Neto, Luiz (Phytotaxa, 2021)
Pseudolaelia Campos Porto & Brade (1935: 209) is a small orchid genus in subtribe Laeliinae. Its phylogenetic affinities place it near several small, endemic genera which constitute an isolated lineage in eastern Brazil, together with Adamantinia Van den Berg & Gonçalves (2004: 231), Constantia Barbosa Rodrigues (1877: 78), Isabelia Barbosa Rodrigues (1877: 75) and Leptotes Lindley (1833: t. 1625). All these genera have comparatively fewer species within the subtribe, and the main centre of distribution are the Brazilian Campos Rupestres, and other granitic rocky outcrops in the Brazilian States of Minas Gerais, Espírito Santo, Rio de Janeiro and Bahia. Also, several species in Pseudolaelia, Constantia and Leptotes are epiphytes on Vellozia sp., considered a very specialized type of epiphytism (van den Berg et al. 2006, Porembsky 2008).